Analysis of the response regulatory network of pepper genes under hydrogen peroxide stress - Tang, Bingqian; Yang, Guangbin; Du, Juan; Xie, Lingling; Wang, Jin; Pan, Luzhao; Luo, Yin; Shan, Qingyun; Zou, Xuexiao; Xiong, Cheng; Liu, Feng (Frontiers in Plant Science, 2022)
Hydrogen peroxide (H2O2) is a regulatory component related to plant signal transduction. To better understand the genome-wide gene expression response to H2O2 stress in pepper plants, a regulatory network of H2O2 stress-gene expression in pepper leaves and roots was constructed in the present study. We collected the normal tissues of leaves and roots of pepper plants after 40 days of H2O2 treatment and obtained the RNA-seq data of leaves and roots exposed to H2O2 for 0.5–24 h. By comparing the gene responses of pepper leaves and roots exposed to H2O2 stress for different time periods, we found that the response in roots reached the peak at 3 h, whereas the response in leaves reached the peak at 24 h after treatment, and the response degree in the roots was higher than that in the leaves. We used all datasets for K-means analysis and identified the clusters related to stress response and related genes. In addition, CaEBS1, CaRAP2, and CabHLH029 were identified through a co-expression analysis and were found to be strongly related to several reactive oxygen species-scavenging enzyme genes; their homologous genes in Arabidopsis showed important functions in response to hypoxia or iron uptake. This study provides a theoretical basis for determining the dynamic response process of pepper plants to H2O2 stress in leaves and roots, as well as for determining the critical time and the molecular mechanism of H2O2 stress response in leaves and roots. The candidate transcription factors identified in this study can be used as a reference for further experimental verification.